Subcontractors' approaches to risk management at project planning stage - Ahmad Zaini, Afzan; Endut, Intan Rohani; Takim, Roshana (2011)
The construction industry is still plagued by poor quality, poor workmanship, poor safety and health environment, and poor practices. The current main problems in the Malaysian construction Industry are landslides in Cameron Highlands caused by development project and delayed projects under the Ninth Malaysia Plan. The idea of introducing formal risk assessment among Malaysian subcontractors during the project planning stage is a proactive approach to achieve project objectives. Therefore, this research intends to achieve the following objectives: (1) to identify types of risks involved at project planning stage, (2) to investigate the subcontractors' approaches of risk assessment techniques at the project planning stage and (3) to establish subcontractors' risk management (SCRIM) planning stage. The research methodology applied for this research includes literature reviews and interviews. Findings from this research found that there is no formal risk management framework being used by Malaysian subcontractor. Therefore, the idea of establishing the SCRIM framework among Malaysian contractors is paramount and justified. Hence, it is suggested that these subcontractors should try to implement SCRIM as a guidelines to mitigate project risks at project planning stage.